2012
DOI: 10.1111/ijfs.12041
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of ultrasonic‐assisted extraction of polyphenols from apple peel employing cellulase enzymolysis

Abstract: Cellulase enzymolysis extraction with ultrasonic-assisted technology was applied for polyphenols extraction from apple peel, and response surface methodology was used to optimise the conditions of polyphenols extraction. Efficiency of extraction was optimised by measuring total polyphenol content and three individual polyphenols. Three independent variables that were taken into consideration were extraction time (X 1 ), extraction temperature (X 2 ) and enzyme amount (X 3 ). The statistical analysis indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…During the pretreatment of US and MW, some of polyphenol compounds coating on the surface of starch granules could be removed, making the extracted sago starch whiter than that obtained from the control method. Junjian et al reported that ultrasonic pretreatment assisted the extraction of polyphenols from apple peels. In contrast, sago starch extracted with enzymatic pretreatment of both EZ and US/EZ had L* values (92.60 and 92.63, respectively) lower than the control starch.…”
Section: Resultsmentioning
confidence: 99%
“…During the pretreatment of US and MW, some of polyphenol compounds coating on the surface of starch granules could be removed, making the extracted sago starch whiter than that obtained from the control method. Junjian et al reported that ultrasonic pretreatment assisted the extraction of polyphenols from apple peels. In contrast, sago starch extracted with enzymatic pretreatment of both EZ and US/EZ had L* values (92.60 and 92.63, respectively) lower than the control starch.…”
Section: Resultsmentioning
confidence: 99%
“…The extraction of polyphenols was performed according to the method described by Ran et al with minor modifications [ 28 ]. Flesh apple pomace was ground into powder in liquid N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The total polyphenol content (TPC) of five extracts was determined by a Folin-Ciocalteu method [ 28 ] and calculated as milligram gallic acid equivalent per gram of powder (mg GAE/g powder).…”
Section: Methodsmentioning
confidence: 99%
“…For efficient recovery of polyphenols from apple pomace, methanol, acetone and their aqueous solutions are commonly used (Wijngaard & Brunton, 2009). Recently, different nonconventional methods (ultrasound, microwaves, pulsed electric fields, high-voltage electrical discharges,) have been proposed to intensify extraction of polyphenols (Bai et al, 2010;Dons ı et al, 2010;Junjian et al, 2013;Acosta-Estrada et al, 2014;Ameer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%